(untitled) (Economic studies journal, 2020)
This study aims to identify the role of the use of information technology in improving the quality of the accounting information system output and its contribution to the promotion of economic development in the Foundation of the Social Security Fund in Libya, where the questionnaire was used as a tool for data collection, and represents the study community in the Board of Directors, branch managers and heads of Accounting and internal auditing departments, in addition to the accountants and internal auditors in the public administration and branches of this institution, while the sample of the study was limited to workers from the above categories in Benghazi, the number of forms distributed (85) retrieved them (70), all of which form a valid analysis. The study found that the use of information technology in the Foundation of Social Security Fund contributes to improve the quality of the outputs of the accounting system by contributing to the acquisition of these outputs for the qualitative characteristics of information, namely: relevance, reliability, understandability, comparability, and also found that the use of information technology contributes In promoting economic development.